The Urgency of Reforming Intellectual Property Law Regulations in Responding to the Development of Artificial Intelligence Technology - Randy Vallentino Neonbeni; Yohanna YR Watofa; Joko Suranto (PT. Radja Intercontinental Publishing, 2026)
The rapid development of artificial intelligence has created significant legal challenges for intellectual property law, particularly regarding authorship, ownership, originality, the use of protected works as training data, and liability for AI-generated outputs. This study aims to analyze the urgency of reforming Indonesian intellectual property law regulations in responding to artificial intelligence technology, with specific focus on the adequacy of copyright, patent, electronic information, personal data protection, and artificial intelligence ethics regulations. This research employs a normative juridical method using statutory and conceptual approaches. Data were collected through library research by examining primary legal materials, including Indonesian laws and regulations, and secondary legal materials consisting of academic literature and policy documents; because this is normative legal research, no respondents or informants were involved. The data were analyzed qualitatively through legal interpretation and systematic analysis. The findings show that existing regulations provide partial protection for human-created works, technological inventions, electronic systems, and personal data, but they do not specifically regulate AI-generated works, ownership of AI outputs, copyrighted data used for AI training, or legal responsibility among users, developers, and platforms. The study concludes that regulatory reform is necessary to strengthen legal certainty, protect creators, and support responsible AI innovation in Indonesia.